Extraperitoneal versus transperitoneal cesarean section in surgical morbidity in a tertiary care centre - S., Bebincy D.; J., Chitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To test the advantages of extraperitoneal cesarean section over transperitoneal cesarean section. Methods: It is a single blinded prospective study. Women who were planned for emergency LSCS in the department of OG, Kanyakumari Government Medical College, Asaripallam were randomly allocated into extraperitoneal cesarean section (ECS) (n=80) or transperitoneal cesarean section (TCS) (n=80) from November 2015 to January 2017 and evaluated. Results: Even though the time taken to deliver the baby was more in ECS group (Average 4:57 minutes) than TCS group (Average 2:05 minutes, there is no change in Apgar score at 1 minute. The postoperative pain measured by VAS was lesser (4.28) in ECS than TCS (7.06). Bowel function returned early in ECS (8.687 hours) than in TCS (16.487 hours) group. None of the cases in ECS group had peroperative vomiting or post-operative wound infection. Conclusions: So, we can conclude that ECS is a better method in experienced hands than the TCS in selected cases.